Digital Financial Services as a Driver for Enhancing Financial Inclusion in Nepal - Adhikari, Santosh (Medha: A Multidisciplinary Journal, 2025)
Financial inclusion is increasingly recognized as a cornerstone of inclusive economic growth and poverty alleviation, especially in developing economies. In Nepal, the expansion of digital financial services (DFS)—including mobile banking, digital wallets, and interoperable payment systems—has transformed access to financial products, particularly for rural and marginalized populations. This paper examines how DFS has driven financial inclusion in Nepal between 2020 and 2025 by synthesizing secondary data from national policy frameworks, financial inclusion indices, and empirical research. Results indicate that the proliferation of mobile and internet penetration, coupled with strong regulatory initiatives such as the National Payment System Development Strategy and Retail Payment Strategy, has elevated account ownership and usage among adults from 58% in 2017 to 83% in 2023. DFS has also narrowed gender and geographic divides, facilitated remittance digitization, and enhanced resilience among low-income households. Despite these advances, challenges persist in digital literacy, affordability, cybersecurity, and gendered social barriers. The study concludes that inclusive DFS growth in Nepal depends on continued investment in digital infrastructure, regulatory innovation, and targeted literacy programs to ensure equitable access and sustainable impact.